2014
DOI: 10.1093/molbev/msu335
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamically Evolving Nematocyst Content of an Anthozoan, a Scyphozoan, and a Hydrozoan

Abstract: Nematocytes, the stinging cells of cnidarians, are the most evolutionarily ancient venom apparatus. These nanosyringe-like weaponry systems reach pressures of approximately 150 atmospheres before discharging and punching through the outer layer of the prey or predator at accelerations of more than 5 million g, making them one of the fastest biomechanical events known. To gain better understanding of the function of the complex, phylum-specific nematocyst organelle, and its venom payload, we compared the solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
133
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(146 citation statements)
references
References 106 publications
10
133
0
3
Order By: Relevance
“…We did not find any of the 167 nonactiniarian cnidarian toxin sequences in the transcriptomes of our focal taxa. This corroborated previous investigations into lineage-specific venom compositions among cnidarians (Rachamim et al 2014). …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…We did not find any of the 167 nonactiniarian cnidarian toxin sequences in the transcriptomes of our focal taxa. This corroborated previous investigations into lineage-specific venom compositions among cnidarians (Rachamim et al 2014). …”
Section: Resultssupporting
confidence: 91%
“…Of the better studied sea anemone toxin genes, voltage-gated sodium channel toxins (NaTxs) and type I and III voltage-gated potassium channel toxins (KTxs) appear to be specific to Actiniaria, with pore forming cytolysins found throughout Cnidaria (Frazao et al 2012). Many of the poorly studied toxin candidates are members of large gene families and share a strong resemblance to their nonvenomous counterparts (Fry et al 2009; Moran et al 2013; Rachamim et al 2014) or have been characterized in only one or two species (Frazao et al 2012). Previous tissue-specific investigations focusing on venom assays of crude extracts or isolated proteins have found that nematocyst type and abundance do not always correlate with venom potency (Hessinger 1988; Nevalainen et al 2004), that tissues thought to be devoid of nematocysts also have high concentrations of venom (Mathias et al 1960), and that whole tissue extracts can contain more potent bioactive compounds when compared with isolated peptides (Hessinger and Lenhoff 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Coral-associated hydrozoans possess specialized polyp morphologies (called 'dactylozoids') dedicated exclusively to defend the colony [17], which are armed with venomous nematocysts capable of injecting a substance whose composition is substantially different from that released by anthozoans [29]. Furthermore, studies on related groups suggest that coralassociated hydrozoans may be hardly palatable due to noxious secondary metabolites, which could provide them with an additional, chemical defense against predators [30].…”
Section: Introductionmentioning
confidence: 99%
“…Tentacles from the jellyfish Rhopilema nomadica [14] were collected from Haifa Bay, Israel, and their large isorhiza nematocysts were isolated as described in Rachamim et al [3] and activated with 1% subtilisin (Sigma). The nematocysts were trapped, activated and their elongation was measured in a microfluidic platform that was specially designed for this study (figure 1).…”
Section: Experimental Methodsmentioning
confidence: 99%